1995
DOI: 10.1159/000227419
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the Arylamine N-Acetyltransferase Polymorphism in Breast Cancer Patients

Abstract: The association of the arylamine N-acetyltransferase polymorphism and breast cancer has been investigated by analysis of genomic DNA from 160 breast cancer patients and 132 healthy women. Five mutations of the NAT2 gene were studied by using allele-specific PCR amplification and restriction mapping with the endonucleases FoKI and Ddel. Eight allelic variants of the NAT2 gene were identified in both, patients with breast cancer and control groups, with relative frequencies. Wild-type 0.194 and 0.219, 341C+481T+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…Shortly afterwards, three phenotyping studies with larger sample sizes reported negative findings [34][35][36]. The first NAT2 genotyping study in patients with breast cancer was published in 1995 and indicated no association of NAT2 polymorphisms and cancer risk [37]. Since then, several studies have addressed the role of NAT polymorphism alone, and the interaction of polymorphisms with smoking in breast cancer risk.…”
Section: Breast Cancermentioning
confidence: 99%
“…Shortly afterwards, three phenotyping studies with larger sample sizes reported negative findings [34][35][36]. The first NAT2 genotyping study in patients with breast cancer was published in 1995 and indicated no association of NAT2 polymorphisms and cancer risk [37]. Since then, several studies have addressed the role of NAT polymorphism alone, and the interaction of polymorphisms with smoking in breast cancer risk.…”
Section: Breast Cancermentioning
confidence: 99%
“…145 The population frequency of the fast acetylator genotype of the NAT2 gene is 22-78%. [145][146][147] None of seven studies found an increased breast cancer risk for the slow acetylator NAT2 phenotype, [148][149][150][151][152][153][154] while two studies found a decreased breast cancer risk. 148 153 No association with breast cancer risk was found when all studies were combined.…”
Section: Nat2mentioning
confidence: 99%
“…Many studies have evaluated the potential role of NAT2 genotypes in breast cancer development and the risk modification of the effect of smoking on breast cancer by the polymorphisms of this gene . Agundez et al firstly reported that the rapid acetylator NAT2 genotypes might be associated with a risk to develop lobular breast cancer, but no support for an association between NAT2 polymorphisms and breast cancer risk was provided [8]. Conversely, Ambrosone et al reported that breast cancer risk was specifically increased in postmenopausal women with the slow acetylator NAT2 genotypes [9].…”
Section: Introductionmentioning
confidence: 99%